2014
DOI: 10.1093/bja/aeu136
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of impedance cardiography for evaluating trends in cardiac output: a comparison with oesophageal Doppler

Abstract: ICG appears to be a reliable method for the non-invasive monitoring of CO in patients undergoing general surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 53 publications
0
28
1
Order By: Relevance
“…All patients underwent physical examination, electrocardiography (ECG), echocardiography, impedance cardiography (ICG), oxygen saturation measurements and laboratory tests. There are many studies that confirmed ICG as a reliable and cost-effective method of haemodynamic assessment in different groups of patients [12][13][14][15]. Impedance cardiography.…”
Section: Methodsmentioning
confidence: 99%
“…All patients underwent physical examination, electrocardiography (ECG), echocardiography, impedance cardiography (ICG), oxygen saturation measurements and laboratory tests. There are many studies that confirmed ICG as a reliable and cost-effective method of haemodynamic assessment in different groups of patients [12][13][14][15]. Impedance cardiography.…”
Section: Methodsmentioning
confidence: 99%
“…Bio-impedance measures the changes in amplitude of the voltage change across the thorax [97]. Both positive and negative studies have been published, with some suggesting bio-impedance to be a useful non-invasive method to assess extracellular volume changes in patients undergoing cardiac surgery, with a close relationship with thermodilution [98,99], while others reported a negative correlation between the accuracy of bio-impedance and increased fluid accumulation within the thorax [100][101][102]. Bio-impedance systems are sensitive to intra-thoracic fluids, such as in patients with oedema or pleural fluid, often present in critically ill patients.…”
Section: Bio-impedance and Bio-reactancementioning
confidence: 99%
“…Impedance cardiography (ICG) is an inexpensive, non-invasive technique that measures changes in transthoracic electric resistance (bioimpedance) in order to estimate phasic alternations in the blood flow [17,18]. Validity, accuracy and repeatability of the results acquired by ICG have been confirmed in various comparative studies [19][20][21]. ICG is not only a useful tool for scientific studies but it also has prognostic value for hypertensive patients [22].…”
Section: Introductionmentioning
confidence: 99%